Interleukin-34 Limits the Therapeutic Effects of Immune Checkpoint Blockade - Naoki Hama (iScience, 2020)
Summary: Interleukin-34 (IL-34) is an alternative ligand to colony-stimulating factor-1 (CSF-1) for the CSF-1 receptor that acts as a key regulator of monocyte/macrophage lineage. In this study, we show that tumor-derived IL-34 mediates resistance to immune checkpoint blockade regardless of CSF-1 existence in various murine cancer models. Consistent with its immunosuppressive characteristics, the expression of IL-34 in tumors correlates with decreased frequencies of cellular (such as CD8+ and CD4+ T cells and M1-biased macrophages) and molecular (including various cytokines and chemokines) effectors at the tumor microenvironment. Then, a neutralizing antibody against IL-34 improved the therapeutic effects of the immune checkpoint blockade in combinatorial therapeutic models, including a patient-derived xenograft model. Collectively, we revealed that tumor-derived IL-34 inhibits the efficacy of immune checkpoint blockade and proposed the utility of IL-34 blockade as a new strategy for cancer therapy.